Geosmithia Species Associated With Bark Beetles From China, With the Description of Nine New Species - Zhang, Xiuyu; Li, You; Si, Hongli; Zhao, Guoyan; Kolařík, Miroslav; Hulcr, Jiri; Jiang, Xiaoqian; Dai, Meixue; Chang, Runlei (Frontiers in Microbiology, 2022)
Fungi of the genus Geosmithia are frequently associated with bark beetles that feed on phloem on various woody hosts. Most studies on Geosmithia were carried out in North and South America and Europe, with only two species being reported from Taiwan, China. This study aimed to investigate the diversity of Geosmithia species in China. Field surveys in Fujian, Guangdong, Guangxi, Hunan, Jiangsu, Jiangxi, Shandong, Shanghai, and Yunnan yielded a total of 178 Geosmithia isolates from 12 beetle species. The isolates were grouped based on morphology. The internal transcribed spacer, β-tubulin, and elongation factor 1-α gene regions of the representatives of each group were sequenced. Phylogenetic trees were constructed based on those sequences. In total, 12 species were identified, with three previously described species (Geosmithia xerotolerans, G. putterillii, and G. pallida) and nine new species which are described in this paper as G. luteobrunnea, G. radiata, G. brevistipitata, G. bombycina, G. granulata (Geosmithia sp. 20), G. subfulva, G. pulverea (G. sp. 3 and Geosmithia sp. 23), G. fusca, and G. pumila sp. nov. The dominant species obtained in this study were G. luteobrunnea and G. pulverea. This study systematically studied the Geosmithia species in China and made an important contribution to filling in the gaps in our understanding of global Geosmithia species diversity.